Factors Affecting the Uniformity of Sign Language: Perceptions of Teachers of Students with Hearing Impairment - Rehmat Ali, Zainab; Kanwal, Asma; Ishrat, Ghazala (Annals of Human and Social Sciences, 2023)
The main purpose of this study was to examine the perception of teachers of students with hearing impairment (SWHI) about the factors affecting the uniformity of the sign language. The nature of study was quantitative. The population of the study was teachers of SWHI. Sample of the study teachers was 100 (M=52, F=48) of students with hearing impairment selected through convenient sampling techniques from different special education institutions. Survey method was used to collect data through self-developed questionnaire with reliability coefficient (α= 0.72). statistical measures were used to analyse the data. The result of the study highlight. This study used to find the variation in sign language which effect on teachers and students. There is no professional development for teachers per-service and in service. The study showed that teachers of students with hearing impairment faced many issues due to the variation of the sign language when students use different signs in the classroom and teachers also learned different signs. And the school did not pay attention on the professional development of the teachers that teachers can use same standard sign language. School and government should pay attention on the development of per-service and in-service teachers in accordance with Pakistan sign language.